The teaching of environmental chemistry: Experimentation as a potentiator of meaningful learning on the subject of air pollution (Research, Society and Development, 2024)
Contemporary challenges are faced in the construction of a society concerned and committed to the preservation of the environment, in such a way that this theme, when approached in Environmental Chemistry classes, contributes to the development of values, behaviors and attitudes in students. This article presents a proposal for applied experimentation aiming to promote meaningful learning in the teaching of Environmental Chemistry on the topic of atmospheric pollution, using Passive Sampling (AP) for Nitrogen Dioxide gas (NO2(g)).The survey was carried out at the IFCE/Caucaia-CE, in the period from March to June of 2023, with 2nd and 3rd year high school classes, in Analytical Chemistry. The methodological procedures of the activities followed the following steps: development of the passive sampler; survey of prior knowledge; presentation of the theme; description and execution of the experimental activity of NO2(g); evaluation of the perception of learning and the didactic resource. The results obtained showed the construction of a low-cost and reusable PVC AP kit. In addition, the analysis of prior knowledge showed that students have some knowledge on the subject. The assessment of the perception of learning and experimentation showed that the technical and theoretical training given to students motivates and facilitates meaningful learning on the subject. In this context, applied experimentation in order to favor meaningful learning in the teaching of Environmental Chemistry is a great alternative and a great ally to make teaching and learning of high school students from public/technical schools more attractive, effective and meaningful.